Research of the foreign countries experience in regulation of investment processes in building sphere - Shlafman, N.; Frolina, K. (Економічний вісник Донбасу, 2017)
The article describes the study of the experience of foreign countries in the regulation of investment processes in the construction industry. Analysis of the experience of foreign countries in the field of state regulation and stimulation of investment in construction can help develop new, effective mechanisms for implementing state policy in the field of residential, industrial and infrastructure construction, establishing and expanding international cooperation in the construction sector, creating opportunities for attracting investment in housing and industrial construction, including foreign ones.
The analysis of housing financing systems in developed countries of the world (USA, England, Germany, France) shows that they are based on a variety of specialized financial institutions - construction and savings, mortgage companies, investment banks, credit unions, as well as on several financial technologies: construction savings, mortgage lending, a certain combination of other, public and private financing, as well as various mixed forms of public and private funding. In these countries the state possesses and active market instruments of state regulation of investment processes through mortgage markets, secondary loans using state (or semi-public) financial institutions.
The analysis of the state of legal regulation in the investment sphere of Ukraine, the development of the securities market and investment trends in the real estate market, and the practice of state regulation of investment and construction processes in Ukraine testify to the expediency of adapting the experience of developed countries to the methods of state regulation of investment activity in the construction sphere to Ukraine, which may become an essential direction of intensification of investment processes in the country. У статті досліджено досвід зарубіжних країн у регулюванні інвестиційних процесів у будівельній сфері. Аналіз досвіду зарубіжних країн щодо державного регулювання і стимулювання інвестиційної діяльності в будівництві може допомогти розробити нові, ефективні механізми реалізації державної політики в галузі житлового, промислового та інфраструктурного будівництва, у налагодженні і розширенні міжнародного співробітництва в будівельній сфері, створенні можливостей залучення інвестицій у житлове і промислове будівництво, у тому числі іноземних.
Аналіз систем фінансування будівництва житла у розвинутих країнах світу (США, Англії, Німеччині, Франції) свідчить, що вони базуються на різноманітності спеціалізованих фінансових інститутів – будівельно-ощадних, іпотечних компаніях, інвестиційних банках, кредитних спілках, а також на кількох фінансових технологіях: будівельних заощадженнях, іпотечному кредитуванні, певного поєднання одного з іншим, державному та приватному фінансуванні, а також на різноманітних змішаних формах державного та приватного фінансування. У цих країнах держава володіє і дійовими ринковими інструментами державного регулювання інвестиційних процесів через ринки закладних, вторинних кредитів із використанням державних (чи напівдержавних) фінансових інститутів.
Проведений аналіз стану правового регулювання в інвестиційній сфері України, розвитку ринку цінних паперів та інвестиційних тенденцій ринку нерухомості, практики державного регулювання інвестиційно-будівельних процесів в Україні свідчить про доцільність адаптації досвіду розвинутих країн щодо методів державного регулювання інвестиційної діяльності в будівельній сфері в України, що може стати суттєвим напрямом активізації інвестиційних процесів в країні. В статье исследован опыт зарубежных стран в регулировании инвестиционных процессов в строительной сфере. Анализ опыта зарубежных стран по государственному регулированию и стимулированию инвестиционной деятельности в строительстве может помочь разработать новые, эффективные механизмы реализации государственной политики в области жилищного, промышленного и инфраструктурного строительства, налаживании и расширении международного сотрудничества в строительной сфере, создании возможностей привлечения инвестиций в жилищное и промышленное строительство, в том числе иностранных.
Анализ систем финансирования строительства жилья в развитых странах мира (США, Англии, Германии, Франции) свидетельствует, что они базируются на разнообразии специализированных финансовых институтов – строительно-сберегательных, ипотечных компаниях, инвестиционных банках, кредитных союзах, а также на нескольких финансовых технологиях: строительных сбережениях, ипотечном кредитовании, определенного сочетания одного с другим, государственном и частном финансировании, а также на различных смешанных формах государственного и частного финансирования. В этих странах государство владеет и действующими рыночными инструментами государственного регулирования инвестиционных процессов через рынки закладных, вторичных кредитов с использованием государственных (или полугосударственных) финансовых институтов.
Проведенный анализ состояния правового регулирования в инвестиционной сфере Украины, развития рынка ценных бумаг и инвестиционных тенденций рынка недвижимости, практики государственного регулирования инвестиционно-строительных процессов в Украине свидетельствует о целесообразности адаптации опыта развитых стран касательно методов государственного регулирования инвестиционной деятельности в строительной сфере, в Украине, что может стать существенным направлением активизации инвестиционных процессов в стране.